TikTok as an Alternative Learning Space: The Phenomenon of Live Streaming Learning - Meidina, Aulia Putri (Komunikator, 2025)
In recent years, short-video platforms such as TikTok have rapidly grown beyond entertainment, increasingly being used as spaces for knowledge sharing and learning space. This trend raises questions about the phenomenon of using live streaming on TikTok as an informal learning space in Indonesia, with a case study of the @mbahgurumatematika account. Employing a study case method within an qualitative approach, the author observes patterns of content delivery, audience interaction, and the application of Vygotsky’s social constructivism theory, particularly the concepts of scaffolding and the zone of proximal development (ZPD). The findings indicate that a slow and structured teaching style enhances the understanding of mathematics, fosters the formation of a learning community, and facilitates collaborative interaction. The article concludes that TikTok can serve as a participatory alternative learning medium, although it cannot replace formal education.